Knowledge, attitudes and behaviours towards people with HIV and AIDS among private higher education students in Johannesburg, South Africa - Natasha Khamisa; Maboe Mokgobi; Tariro Basera (AOSIS, 2020)
Background: Human immunodeficiency virus and acquired immunodeficiency syndrome (HIV and AIDS) is a global health and social problem, with South Africa having an estimated overall prevalence rate of 13.5%. Compared to young male participants, young female participants have been reported to have less knowledge about HIV and AIDS, including prevention strategies, and this is associated with risky sexual behaviours and negative attitudes towards condom use. Objectives: The study investigated gender differences in knowledge, attitudes and behaviours towards HIV and AIDS among 542 private higher education students in Johannesburg, South Africa. Method: Participants completed an online structured questionnaire measuring knowledge, attitudes and behaviours as well as demographics (including age, gender and relationship status). Results: The results indicate that overall there were no significant differences between male and female students in terms of HIV and AIDS knowledge. However, female students had significantly less knowledge with regard to unprotected anal sex as a risk factor for HIV and AIDS. In addition, young female students reported condom use at last sex less frequently than male students. Nonetheless, both genders reported a positive attitude towards condom use and towards people living with HIV and AIDS. Conclusion: It is recommended that the relevant authorities at the state and the higher education level seriously consider implementing specific strategies for preventing HIV and AIDS through improved knowledge, attitudes and behaviours among young females.